GTPase ROP2 binds and promotes activation of target of rapamycin, TOR, in response to auxin. (28th February 2017) - Schepetilnikov, Mikhail; Makarian, Joelle; Srour, Ola; Geldreich, Angèle; Yang, Zhenbiao; Chicher, Johana; Hammann, Philippe; Ryabova, Lyubov A
Abstract: Target of rapamycin (TOR) promotes reinitiation at upstream ORFs (uORFs) in genes that play important roles in stem cell regulation and organogenesis in plants. Here, we report that the small GTPase ROP2, if activated by the phytohormone auxin, promotes activation of TOR, and thus translation reinitiation of uORF‐containing mRNAs. Plants with high levels of active ROP2, including those expressing constitutively active ROP2 (CA‐ROP2), contain high levels of active TOR. ROP2 physically interacts with and, when GTP‐bound, activates TOR in vitro . TOR activation in response to auxin is abolished in ROP‐deficient rop2 rop6 ROP4 RNAi plants. GFP‐TOR can associate with endosome‐like structures in ROP2‐overexpressing plants, indicating that endosomes mediate ROP2 effects on TOR activation. CA‐ROP2 is efficient in loading uORF‐containing mRNAs onto polysomes and stimulates translation in protoplasts, and both processes are sensitive to TOR inhibitor AZD‐8055. TOR inactivation abolishes ROP2 regulation of translation reinitiation, but not its effects on cytoskeleton or intracellular trafficking. These findings imply a mode of translation control whereby, as an upstream effector of TOR, ROP2 coordinates TOR function in translation reinitiation pathways in response to auxin. Synopsis: Small GTPase ROP2 is a new component of the auxin‐responsive TOR signaling pathway, in which ROP2 activated by auxin promotes TOR activation and up‐regulation of translation of mRNAs that harbor uORFs within their leaders. Small GTPase ROP2 interacts with TOR in Arabidopsis . TOR is phosphorylated and activated in response to auxin via GTP‐bound ROP2. ROP2 promotes TOR accumulation on endosome‐like structures. GTP‐bound ROP2 promotes both polysome loading and translation reinitiation of mRNAs that harbor uORFs within their leaders in a TOR‐responsive manner. Abstract : Auxin signaling activates the small GTPase ROP2, causing TOR activation and increased translation of uORF‐containing mRNAs, thus making ROP2 the intervening link between auxin signaling and TOR‐dependent translation control.